2018
DOI: 10.1080/02786826.2018.1457767
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the absorption Ångström exponent and its relation to physicochemical properties for mini-CAST soot

Abstract: In this work, a mini-CAST soot generator was used to produce soot with different optical and physicochemical characteristics. Absorption A ngstr€ om exponents (AAE) expressing the absorption wavelength dependence were assessed by multiwavelength in-situ and filter-based (aethalometer) laser extinction. The two optical techniques showed good agreement. For the chosen mini-CAST operating conditions, AAEs between 1 and 3.5 were found. Soot with high mass-fractions of organic carbon (OC) and pyrolytic carbon (PC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…Therefore, in contrast to the present study, small particles were always associated with a low EC content even at fuellean conditions. Török et al (2018) tuned the particle size (miniCAST 5201C) mostly by diluting propane with nitrogen at slightly fuel-rich conditions. The higher the dilution factor the smaller was the GMD (100-300 nm) and the higher the AAE (∼1-3.5) and OC/TC ratio (>10 to ∼50%) of the particles.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in contrast to the present study, small particles were always associated with a low EC content even at fuellean conditions. Török et al (2018) tuned the particle size (miniCAST 5201C) mostly by diluting propane with nitrogen at slightly fuel-rich conditions. The higher the dilution factor the smaller was the GMD (100-300 nm) and the higher the AAE (∼1-3.5) and OC/TC ratio (>10 to ∼50%) of the particles.…”
Section: Resultsmentioning
confidence: 99%
“…It is known from basic combustion studies and model flames that soot properties change with decreasing combustion temperature. Non-regulated emissions with health impact such as aromatic compounds [39], including PAHs, may increase as combustion temperature decreases [40].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kahnert et al found that the homogeneous sphere model provided more accurate results than the layered sphere model. Similarly, Torok et al (2018) suggested that soot core and coating is not a good model for laboratory-produced soot. China et al (2015) investigated soot particles transported over long distances.…”
Section: Introductionmentioning
confidence: 99%